Pembentukan Karakter Religius Siswa melalui Metode Pembiasaan di MTs Al-Fathimiyah Karawang - Selly Sonia; Tajuddin Nur; Yayat Herdiana (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
Education plays an important role in the survival of the nation and state. Therefore, the formation of the personality of students in accordance with religious values becomes a necessity and necessity. It is very important to produce religious character values with the habituation method, if the school environment and place of residence are good, it will support all goodness, so that the character values of students will grow well. Religious character is very necessary for students to get the changing times in the era of globalization, in this case students can behave well based on the provisions and provisions of religion. This study aims to determine the religious attitudes of students by instilling behavioral values through habituation methods. The method used in this study is a qualitative descriptive method. The subject of this study is the head of madrasah, educators, curriculum, students. Data collection techniques used through observation, interview, and documentation methods. Data analysis techniques using data reduction, data presentation,conclusion. The results showed the formation of religious character of students with the method of habituation in Madrasah Tsanawiyah Al-Fathimiyah Karawang is habituation 5S (greeting, greetings, smiles, courtesy, courtesy), habituation to be disciplined, honest habituation, habituation worship prayer, and habituation to read the Qur'an.